2018
DOI: 10.3390/inorganics6010011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water Content on Properties of Homogeneous [bmim]Fe(III)Cl4–H2O Mixtures and Their Application in Oxidative Absorption of H2S

Abstract: Abstract:The potential of 1-butyl-3-methylimidazolium tetrachloroferrate ([bmim] O was reduced to FeCl 2 , at the same time, H 2 S was oxidized to S 8 . In addition, the decrease in acidity caused by increasing the water content increased the weight percent of absorbed H 2 S, and decreased volatile HCl emissions. However, it is difficult to prevent the suspended S 8 generated at vol % (H 2 O) ≥ 80% from the formation of sulfur blockage. Therefore, oxidative absorption of H 2 S by [bmim]Fe(III)Cl 4 -H 2 O mixtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, the author did not mention the time and temperature at which this phenomenon occurred. 55 In this instance, we employed a catalyst loading of up to 20 wt% in water at optimized conditions (room temperature, and time, 4 hours) to cross-check this claim with our observation. Fig.…”
Section: Resultsmentioning
confidence: 64%
“…However, the author did not mention the time and temperature at which this phenomenon occurred. 55 In this instance, we employed a catalyst loading of up to 20 wt% in water at optimized conditions (room temperature, and time, 4 hours) to cross-check this claim with our observation. Fig.…”
Section: Resultsmentioning
confidence: 64%
“…The same group demonstrated that the acidity and Fe­(III) concentration of Fe­(III)-ILs have significant influence on the oxidation of H 2 S to S 8 and the reduction of [Bmim]­Fe­(III)­Cl 4 to [Bmim]­Fe­(II)­Cl 4 H by varying molar ratios of [Bmim]­[Cl] and FeCl 3 ·6H 2 O . Meanwhile, in the presence of water, the oxidative-absorption of H 2 S increased, and the emission of volatile HCl decreased with the increase of water content in the range of 5.88–80% . However, high content of water could lead to the decomposition of the organic cations of ILs due to the reaction of water with Fe 2+ and O 2 , and thus only low water content in Fe-based ILs is acceptable.…”
Section: Ils and Dess For Utilization Of H2smentioning
confidence: 99%
“…Cl] and FeCl 3 •6H 2 O 32. Meanwhile, in the presence of water, the oxidative-absorption of H 2 S increased, and the emission of volatile HCl decreased with the increase of water content in the range of 5.88−80% 204. However, high content of water could lead to the decomposition of the organic cations of ILs due to the reaction of water with Fe 2+ and O 2 ,205 and thus only low water content in Fe-based ILs is acceptable.…”
mentioning
confidence: 99%
“…Water accumulated in a desulfurization system could increase the solubility in the desulfurizer and limit sulfur precipitation. Wang and Ding 111 reported that adjusting water content from 5.88% to 80% could regulate the acidity of the [Bmim]FeCl 4 system and increase the H 2 S removal efficiency, yet it is difficult to prevent the formation of sulfur blockage at vol % (H 2 O) ≥ 80%. Lee et al 41 stated that high water content in [Bmim]FeCl 4 can react with Fe 2+ and O 2 to produce •OH radicals, leading to the decomposition of Fe-based ILs organic cations.…”
Section: Oxidative Desulfurization Of H 2 S In Milsmentioning
confidence: 99%